2021
DOI: 10.3390/ma14082006
|View full text |Cite
|
Sign up to set email alerts
|

3D PCL/Gelatin/Genipin Nanofiber Sponge as Scaffold for Regenerative Medicine

Abstract: Recent advancements in tissue engineering and material science have radically improved in vitro culturing platforms to more accurately replicate human tissue. However, the transition to clinical relevance has been slow in part due to the lack of biologically compatible/relevant materials. In the present study, we marry the commonly used two-dimensional (2D) technique of electrospinning and a self-assembly process to construct easily reproducible, highly porous, three-dimensional (3D) nanofiber scaffolds for va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 83 publications
0
13
1
Order By: Relevance
“…28,53 Different studies indicated the PCL/Gel composites for overcoming PCL deficiencies providing suitable biocompatibility, mechanical, and chemical traits. 36,54 Indeed, our in vitro biocompatibility assays demonstrated no difference between conditioned scaffolds and plasma-treated ones, contrary to in vivo biocompatibility results indicating better biocompatibility of conditioned scaffolds than other groups. Our in vitro and in vivo biocompatibility results were similar to those reported by Samadikuchaksaraei et al 26 They investigated the effects of osteoblast-conditioning on mechanics, biocompatibility, and osteoinductivity of a nanohydroxyapatite/gelatin scaffold.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…28,53 Different studies indicated the PCL/Gel composites for overcoming PCL deficiencies providing suitable biocompatibility, mechanical, and chemical traits. 36,54 Indeed, our in vitro biocompatibility assays demonstrated no difference between conditioned scaffolds and plasma-treated ones, contrary to in vivo biocompatibility results indicating better biocompatibility of conditioned scaffolds than other groups. Our in vitro and in vivo biocompatibility results were similar to those reported by Samadikuchaksaraei et al 26 They investigated the effects of osteoblast-conditioning on mechanics, biocompatibility, and osteoinductivity of a nanohydroxyapatite/gelatin scaffold.…”
Section: Discussioncontrasting
confidence: 68%
“…Electrospun PCL scaffolds coated by gelatin improved the proliferation and survival of fibroblast cells in vitro and in vivo 28,53 . Different studies indicated the PCL/Gel composites for overcoming PCL deficiencies providing suitable biocompatibility, mechanical, and chemical traits 36,54 . Indeed, our in vitro biocompatibility assays demonstrated no difference between conditioned scaffolds and plasma‐treated ones, contrary to in vivo biocompatibility results indicating better biocompatibility of conditioned scaffolds than other groups.…”
Section: Discussionmentioning
confidence: 53%
“…Consequently, the use of other materials, such as chitosan, polycaprolactone (PCL), and poly(ethylene glycol) (PEG) has been investigated [4]. To simulate the inherent ECM architecture of skin, with its nanofibrous structure and porosity, electrospinning of these polymers can be employed [42][43][44][45][46]. Despite the evident success of electrospun scaffolds, there are numerous ongoing challenges, such as achieving suitable cell infiltration [43], cell adhesion [47], or mechanical properties [43].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the evident success of electrospun scaffolds, there are numerous ongoing challenges, such as achieving suitable cell infiltration [43], cell adhesion [47], or mechanical properties [43]. Research is mainly focused on biopolymers (e.g., hyaluronic acid, alginate, collagen, silk protein, fibrinogen, chitosan, starch, and poly(3-hydroxybutyrate-co-3-hydroxyvalerate (PHBV)) [48] or on synthetic polymers such as poly(lactic acid-coglycolic acid) (PLGA), PCL or PLA [42,46,48]. To promote cell adhesion, proliferation, migration, or morphology, bioactive molecules are commonly added to the scaffolds, in particular collagen, gelatin, or elastin [47], which are however associated with challenges in terms of batch-to-batch variability or adhesion efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…They found that nonmodified PET-CH revealed quick degradation after 3 days of buffer exposure. Several concentrations of GNP (0.5%, 1.0%, and 2.5%) were also added, by Merk et al (2021) , into polycaprolacton/GEL formulation to produce sponges for regenerative purposes. A remaining mass of >92% was found in all GNP-crosslinked samples after 8 weeks of incubation in buffer solution.…”
Section: Genipin Crosslinking Effect On Biomatrix Propertiesmentioning
confidence: 99%